2010
DOI: 10.1007/s10519-010-9403-8
|View full text |Cite
|
Sign up to set email alerts
|

Food Neophobia in Young Adults: Genetic Architecture and Relation to Personality, Pleasantness and Use Frequency of Foods, and Body Mass Index—A Twin Study

Abstract: Food neophobia has been studied extensively in children, but its causal origins and relationship to eating behavior in adults are not well understood. We studied genetic and environmental effects on variation in food neophobia, measured using the Food Neophobia Scale, and explored associations between food neophobia and personality, pleasantness and use frequency of food groups, and body mass index in young adult twins (N = 1175, aged 20-25 years, 54.7% women). In women, additive genetic effects (heritability)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
128
5
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(160 citation statements)
references
References 38 publications
17
128
5
10
Order By: Relevance
“…If food neophobia decreases during late childhood (McFarlane and Pliner, 1997), the null association may be expected in this age group. However, a recent study of young adults aged 20-25 years reported that food neophobia was inversely associated with use frequency of fruits and vegetables (Knaapila et al, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…If food neophobia decreases during late childhood (McFarlane and Pliner, 1997), the null association may be expected in this age group. However, a recent study of young adults aged 20-25 years reported that food neophobia was inversely associated with use frequency of fruits and vegetables (Knaapila et al, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…Further, food neophobia can refer to the actual, observable behaviour, as well as the trait of an underlying predisposition (tendency) to avoid novel foods. Trait food neophobia resembles personality traits by being rather heritable (3)(4)(5)(6) and stable (7) , and appears to be more resistant to interventions than behavioural food neophobia (8)(9)(10) . Food neophobia protects omnivores against unknown risks, whereas its opposite, seeking novel foods (food neophilia), helps to maximize the advantages of omnivory (1) .…”
Section: Food Neophobia Diet Quality Steps Study Vegetable Consumptionmentioning
confidence: 99%
“…The FNS is a robust, psychometrically validated, and widely used measure of individuals' willingness to try novel and unfamiliar foods (e.g., Knaapila et al, 2011;Olabi, Najm, Baghdadi, & Morton, 2009;Pliner & Hobden, 1992). The FNS instructs participants to rate their level of agreement with 10 statements such as "I don't trust new foods" and "I am constantly sampling new and different foods" (reverse scored) on a 7-point Likert scale (1 = disagree strongly; 7 = agree strongly).…”
Section: Food Neophobiamentioning
confidence: 99%